1998
DOI: 10.1038/sj.ejhg.5200225
|View full text |Cite
|
Sign up to set email alerts
|

A benign polymorphism in the aspartoacylase gene may cause misinterpretation of Canavan gene testing

Abstract: We found normal individuals whose aspartoacylase gene Y231X mutation site consistently gave no signal in a primer extension assay. We determined the nucleotide sequence of the relevant region of the gene in those individuals, and found a new allele with a thymidine residue at the mutation site instead of a cytidine. Since both TAC and TAT code for tyrosine, this sequence polymorphism has no effect on the amino acid sequence of the ASPA protein. We found the relative frequencies of the 693C and the 693T alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
1
4
0
Order By: Relevance
“…This indicates that there is a conserved haplotype containing the 854C mutation and the 693T allele in this population, indicating an ancestral AJ founder for this mutation, as seen in many of the common AJ diseases which have only one or two major disease‐causing mutations. The disequilibrium of the A854C mutation and the 693T allele has also been noted by Propheta et al [1998], who reported allele frequencies for the 693C and T alleles as 0.75 and 0.25, respectively, based on analysis of 101 randomly selected Israeli non‐carrier individuals. In our 1,073 non‐carrier samples tested we found the frequencies for the 693C and T alleles to be 0.69 and 0.31, respectively.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This indicates that there is a conserved haplotype containing the 854C mutation and the 693T allele in this population, indicating an ancestral AJ founder for this mutation, as seen in many of the common AJ diseases which have only one or two major disease‐causing mutations. The disequilibrium of the A854C mutation and the 693T allele has also been noted by Propheta et al [1998], who reported allele frequencies for the 693C and T alleles as 0.75 and 0.25, respectively, based on analysis of 101 randomly selected Israeli non‐carrier individuals. In our 1,073 non‐carrier samples tested we found the frequencies for the 693C and T alleles to be 0.69 and 0.31, respectively.…”
Section: Discussionsupporting
confidence: 60%
“…Reports have appeared of a potential source of misinterpretation of ‘home‐brew’ molecular assays for CD [Alford et al, 1998; Propheta et al, 1998] caused by the 693C/T polymorphism at the site of the C693A (Y231X) mutation. Our assay was designed to detect the reported 693C/T polymorphism seen at the site of C693A (Y231X) mutation.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…There are several reports of TAC to TAT in the aspartoacylase gene; however, both code for tyrosine and so do not change the amino acid substitution. 20,21 In our patient, we observed a tyrosine-to-cysteine change at amino acid position 288 (Y288C) of aspartoacylase resulting from an A to G transition. This amino acid change did not decrease the enzyme activity, indicating polymorphism.…”
Section: Discussionmentioning
confidence: 68%
“…66,67 Quality assurance Laboratories should follow molecular pathology guidelines established by the College of American Pathology (CAP), be in compliance with the NIH-DOE Task Force on Genetic Testing, 68 and follow the ACMG Standards and Guidelines for Clinical Genetics Laboratories. With the exception of GD, an incorrect assignment of homozygous mutant is suggested when the indication is carrier screening.…”
Section: Incorrect Assignment Of Homozygositymentioning
confidence: 99%